MODELLING OF NAGUTSKOE MINERAL WATER FIELD AS A CONTROL OBJECT - Karina Vladikovna Martirosyan; Alexander Vitalievich Martirosyan (Современная наука и инновации, 2022)
In this work the setting of the minera waterl field’s rate of flow controlling problem is considered. As an object of control Nagutskoe mineral water field is considered. At first hydrogeological structure of the field was examined, then mathematical modelhas been developed. Hydrogeological processes’ parameters, which can be used in field’s ate of flow control organization were being mentioned.